Jajasan “Pembaruan”: Propaganda discourse through its printed products - Rhoma Dwi Aria Yuliantri (Informasi, 2021)
The purpose of this paper is to describe Jajasan “Pembaruan” as a publisher that produced printed materials in the form of magazines and books in Indonesia (1950-1966). This study might be categorized in the history of communication as a political frame. This article examines particularly on how Jajasan “Pembaruan” as a political agent carried out propaganda with printed material productions in the form of book and magazine publications. As an agent of trans-nationalism, through the content in the publication, Jajasan “Pembaruan” as well as being a medium in shaping the concept of identity politically and culturally through discourse politics. This research shows that the publications by Jajasan “Pembaruan” were agents of political propaganda pioneered by several young people (political activists and leftist thinkers), the Indonesian Communist Party. Thus, the productions by Jajasan “Pembaruan” were at the same time a strong foundation in providing theory, politics, and practices regarding the idea of a “new way”, especially among the cadres of the Indonesian Communist Party about Indonesian political identity. Propaganda spread through books or magazines published by Jajasan “Pembaruan” was one of the discourse efforts of “decolonialization” in spreading various communist political views. Production or printed materials by Jajasan “Pembaruan” received support in a fluid communication network between countries in the context of the cold war.